Space charge separation MoS2 / CdS composite photocatalyst as well as preparation method and application thereof
By synthesizing MoS2/CdS composite photocatalysts in the photocatalytic system, and growing on CdS nanorods with MoS2 cocatalysts, the directional migration of photogenerated electrons is achieved, solving the problems of low photocatalytic hydrogen production efficiency and high cost of precious metals, significantly improving The efficiency and stability of photocatalytic hydrogen production are achieved.
Patent Information
- Application Number
- CN202411201407.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-24
AI Technical Summary
In the existing photocatalytic systems, the photogenerated carrier separation efficiency is low, the precious metal-based cocatalyst is high, and the migration of electron-hole pairs is undirected, which limits the efficiency of photocatalytic hydrogen production.
MoS2/CdS composite photocatalyst is synthesized by a one-step hydrothermal method, and CdS nanorods are prepared using cadmium acetate and thioacetamide, and MoS2 cocatalysts with electron harvesting function are grown at one end to form a cluster structure and realize electron-holes Directed migration for the right.
The efficiency of photocatalytic hydrogen production was significantly improved. The MoS2/CdS composite photocatalyst showed excellent catalytic activity and stable hydrogen evolution activity under simulated sunlight conditions. The hydrogen production performance reached 26.7 times that of blank CdS, and it was tested over a long period of time. Stay stable in the middle.
Smart Images

Figure CN119175104A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysts, and relates to a MoS2 / CdS composite photocatalyst with directional spatial charge separation capability, and preparation and application thereof. Background Art
[0003] Hydrogen (H2) has a high mass energy density and its combustion process can achieve zero carbon emissions throughout the process, making it an excellent energy carrier and a potential candidate for future low-carbon energy systems. Photocatalytic technology has attracted much attention because it can use renewable sunlight as a driving force to decompose water to produce hydrogen under mild conditions.
[0004] At present, the limitation of photocatalytic hydrogen production mainly lies in the low separation efficiency of photogenerated charge carriers. Therefore, constructing an efficient and stable photocatalytic system is the key to improving photocatalytic hydrogen production. Some researchers have adopted the strategy of loading precious metal co-catalysts to accelerate the separation efficiency of photogenerated charges and improve hydrogen production efficiency, but precious metal resources are limited and expensive, which limits their large-scale industrial application. Therefore, designing a non-precious metal-based loaded catalytic system is the key to further developing photocatalytic hydrogen production technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low separation efficiency of photogenerated carriers in traditional photocatalytic systems, high cost of using precious metal-based co-catalysts, and restraining the surface recombination of photogenerated electrons induced by non-directional migration, and to provide a photocatalyst that can replace precious metals and in which the generated electron-hole pairs can be directed to migrate and be utilized. The photocatalyst can significantly improve the effect of photolysis of water to produce hydrogen under simulated sunlight conditions.
[0006] The purpose of the present invention is to achieve the following technical means:
[0007] The invention discloses a MoS2 / CdS composite photocatalyst with spatial charge separation capability. The MoS2 / CdS composite photocatalyst is a composite material which uses cadmium acetate as a cadmium source, thioacetamide as a sulfur source, and ethylenediamine as a reaction solvent, and synthesizes CdS nanorods by a one-step hydrothermal method, and then grows a MoS2 co-catalyst with an electron harvester function at one end of the CdS nanorods.
[0008] The length of the CdS nanorod is about 1 to 3 μm.
[0009] The molar ratio of the cadmium acetate to thioacetamide is 1:2.
[0010] The MoS2 co-catalyst presents a cluster structure. The loading amount of MoS2 on the CdS nanorods can be achieved by controlling the addition amount of the precursor (NH4)2MoS4. The loading amount of MoS2 on the CdS nanorods is 10.3wt% to 46.2wt%, specifically, 10.3wt%, 21.8wt%, 31.7wt%, 46.2wt%.
[0011] A method for preparing the MoS2 / CdS composite photocatalyst is characterized by comprising the following steps:
[0012] Step (1), preparation of CdS nanorods: using cadmium acetate as a cadmium source, thioacetamide as a sulfur source, and ethylenediamine as a reaction solvent, dissolving cadmium acetate and thioacetamide in ethylenediamine, and performing a hydrothermal reaction. After the reaction is completed, separating the precipitate, and washing it with deionized water and anhydrous ethanol, respectively, to obtain CdS nanorods;
[0013] Step (2), preparation of MoS2 / CdS composite photocatalyst: CdS nanorods are dispersed in a mixed solvent of water and diethylenetriamine, ammonium tetrathiomolybdate is added as a molybdenum source and a sulfur source, reacted under high temperature conditions, and MoS2 clusters are in situ grown on one end of the CdS nanorods by hydrothermal treatment. After the reaction is completed, the product is separated, and the product is washed with deionized water and anhydrous ethanol and dried; in order to improve the crystallization degree of the catalyst and remove the organic solvent molecules on the surface, the product is placed in a tubular furnace and heat-treated with nitrogen as the reaction atmosphere to obtain a MoS2 / CdS composite photocatalyst.
[0014] In step (1), the temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 18 hours.
[0015] In step (2), the mass ratio of ammonium tetrathiomolybdate to thioacetamide is 0.15:1 to 0.70:1.
[0016] In step (2), the reaction temperature is 180°C and the reaction time is 20 hours.
[0017] In step (2), the product is placed in a tubular furnace, with nitrogen as the reaction atmosphere, and the temperature is increased to 400° C. at a heating rate of 5° C. / min, and heat treated at 400° C. for 2 hours.
[0018] Another object of the present invention is the application of the MoS2 / CdS composite photocatalyst to decompose water molecules to produce hydrogen under light conditions.
[0019] A method for catalytically decomposing water molecules to prepare hydrogen comprises: adding a MoS2 / CdS composite photocatalyst into a photocatalytic reactor, using a lactic acid solution as a reaction substrate, and catalytically decomposing water molecules to generate hydrogen under vacuum and light conditions with the MoS2 / CdS composite photocatalyst. In the process, the photogenerated charges generated by the MoS2 / CdS composite photocatalyst are used to catalytically decompose water molecules to generate hydrogen, while the lactic acid is used to consume photogenerated holes, thereby improving the utilization efficiency of electrons and ultimately increasing the rate of hydrogen production by water decomposition.
[0020] The dosage ratio of the MoS2 / CdS composite photocatalyst and the lactic acid solution is 100:60 mg / mL.
[0021] The concentration of the lactic acid solution is 0.25 M. Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention synthesizes CdS nanorods by a one-step hydrothermal method. In order to construct an efficient charge separation photocatalyst system, a MoS2 co-catalyst with an electron harvester function is further grown at one end of the CdS nanorods to improve the performance while avoiding the use of precious metals. Since MoS2 has a strong affinity for photogenerated electrons, photogenerated electrons on the CdS surface are easily transferred, thereby inhibiting the recombination of electron-hole pairs and significantly improving the catalytic activity of active sites on the CdS surface. Control experiments also show that the photogenerated electrons generated by CdS tend to transfer to MoS2 sites, achieving directional migration of charges. The MoS2 / CdS composite photocatalyst of the present invention has excellent catalytic activity and stable hydrogen evolution activity under simulated sunlight conditions.
[0023] Due to the presence of the co-catalyst MoS2, the hydrogen production activity of CdS is significantly improved, and the hydrogen production performance under the optimal loading condition reaches 6.68±0.10mmol g -1 h -1 , which is 26.7 times the hydrogen production effect of blank CdS. The results of long-term cycle experiments show that the composite photocatalyst can continuously and stably produce hydrogen, that is, the photocatalyst has good application prospects in the field of photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Scanning electron microscope (a) and transmission electron microscope (b and c) images of the MoS2 / CdS composite photocatalyst of Example 1.
[0025] Figure 2 This is the X-ray powder diffraction pattern of the MoS2 / CdS composite photocatalyst of Example 1.
[0026] Figure 3 This is the UV-visible-near-infrared absorption spectra of CdS nanorods and MoS2 / CdS composite photocatalyst in Example 1.
[0027] Figure 4 This is the linear sweep voltammetry (LSV) curve of CdS nanorods and MoS2 / CdS composite photocatalyst in Example 1.
[0028] Figure 5 This is a diagram of the hydrogen production performance of the photocatalyst. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below through specific embodiments and drawings.
[0030] Example 1
[0031] A method for preparing a MoS2 / CdS composite photocatalyst, the steps are as follows:
[0032] Step (1), weighing 0.25g (1mmol) of cadmium acetate dihydrate and 0.15g (2mmol) of thioacetamide in 60mL of ethylenediamine, stirring magnetically for 30 minutes to dissolve them, transferring the solution to a 100mL high-pressure reactor, placing the high-pressure reactor in an oven, and performing a hydrothermal reaction at 180°C for 18h. After the reaction is completed, cooling to room temperature, centrifuging, collecting a yellow product, and washing it alternately with deionized water and anhydrous ethanol, and repeating the washing three times to obtain CdS nanorods;
[0033] Step (2), dispersing CdS nanorods in a mixed solvent containing 20mL of diethyltriamine and 4mL of ultrapure water, adding 50mg of ammonium tetrathiomolybdate ((NH4)2MoS4) to the above suspension, and starting magnetic stirring. After stirring for 30 minutes, the suspension is transferred into a 30mL high-pressure reactor, maintained at 180°C for 20 hours, naturally cooled, and centrifuged to obtain a dark green product, which is alternately washed with deionized water and anhydrous ethanol, repeated washing three times, and dried in a vacuum oven; placing the sample in a tubular furnace, heating it to 400°C at a heating rate of 5°C / min in a N2 atmosphere, and heat-treating it at 400°C for 2 hours to obtain a MoS2 / CdS composite photocatalyst, wherein the loading amount of MoS2 in the MoS2 / CdS composite photocatalyst is 21.8wt%.
[0034] like Figure 1 As shown, the CdS nanorod has a nanorod-like structure with a length of about 1 to 3 μm. MoS2 grows on one end of the CdS nanorod and presents a cluster structure.
[0035] The MoS2 / CdS composite photocatalyst was characterized by X-ray powder diffraction, and the crystal form of the sample was consistent with that of standard CdS ( Figure 2 ).
[0036] Comparing MoS2 / CdS photocatalyst with nanorods, it can be clearly observed that MoS2 / CdS photocatalyst has a superior absorption performance in terms of absorbance ( Figure 3 ).
[0037] The LSV curve shows that the MoS2 / CdS composite photocatalyst has excellent kinetic performance for hydrogen evolution ( Figure 4 ).
[0038] Example 2
[0039] Same as Example 1, except that the addition amount of (NH4)2MoS4 is controlled to be 25 mg, and the other steps are consistent with Example 1. The MoS2 loading amount in the MoS2 / CdS composite photocatalyst is 10.3 wt%.
[0040] Example 3
[0041] Same as Example 1, except that the addition amount of (NH4)2MoS4 is controlled to be 75 mg, and the other steps are consistent with Example 1. The MoS2 loading amount of the MoS2 / CdS composite photocatalyst is 31.7 wt%.
[0042] Example 4
[0043] Same as Example 1, except that the amount of (NH4)2MoS4 added was controlled to be 100 mg, and the other steps were consistent with Example 1. The MoS2 loading amount of the MoS2 / CdS composite photocatalyst was 46.2 wt%.
[0044] Comparative Example 1
[0045] The inventors used a hydrothermal method to prepare a composite sample with MoS2 nanosheets loaded on the sidewalls of CdS nanorods, and the method is as follows:
[0046] CdS nanorods (sample prepared in step (1) of Example 1) were dispersed in 24 mL of ultrapure water. 40 mg of sodium molybdate and 160 mg of thioacetamide were added to the suspension and stirred evenly. The suspension was transferred to a 30 mL high pressure reactor and reacted at 180°C for 20 h. The precipitate was taken and washed alternately with deionized water and anhydrous ethanol for three times. The powder was then vacuum dried at 60°C and transferred to a tube furnace for heat treatment at 400°C for 2 h under N2 atmosphere. The loading of MoS2 in the sample was 21.1 wt%.
[0047] Example 5
[0048] The performance of photolysis of water to produce hydrogen was evaluated for different samples, and the steps were as follows: 100 mg of MoS2 / CdS composite photocatalyst (Example 1-Example 4) or CdS nanorods (Example 1) or composite sample (Comparative Example 1) was dispersed in 60 mL of lactic acid (0.25 M) aqueous solution and mixed evenly by ultrasound-assisted means. The evenly dispersed solution was transferred to a photocatalytic reaction vessel and vacuum-degassed. A xenon lamp light source equipped with AM1.5 was turned on to simulate sunlight conditions, and the reaction solution was irradiated, and the temperature of the system was maintained at 5 ° C using circulating condensed water control. At certain intervals, the generated gas was collected by an online trace gas detector device and the hydrogen production rate was analyzed.
[0049] The performance of different samples in generating hydrogen is shown in Figure 2. Figure 5 As shown in the figure, it can be seen that due to the presence of the co-catalyst MoS2, MoS2 has a strong affinity for photogenerated electrons, and the photogenerated electrons on the CdS surface are easily transferred, thereby inhibiting the recombination of electron-hole pairs, significantly improving the catalytic activity of the active sites on the CdS surface, and significantly improving the hydrogen production activity of CdS. The hydrogen production performance at the optimal loading amount (Example 1) reaches 6.68±0.10mmol g -1 h -1 , which is 26.7 times the hydrogen production effect of blank CdS. Under the same co-catalyst loading conditions, the hydrogen production rate of the catalyst in Comparative Example 1 is significantly lower than the hydrogen production effect of the catalyst in Example 1. This is due to the different distribution positions of the co-catalysts. In Example 1 MoS2 / CdS composite photocatalyst, MoS2 is located at the top of the nanorods, so the photogenerated electrons migrate along the nanorods to the top to participate in the reaction, while the photogenerated holes remain on the side walls of the nanorods. The possibility of contact between the two is greatly reduced, and more photogenerated electrons are used to decompose water to produce hydrogen; in contrast, when MoS2 is located on the side walls of the nanorods, the photogenerated electrons and holes will migrate to the side walls at the same time, and the recombination of electron-hole pairs will inevitably occur, reducing the utilization efficiency of the photogenerated electrons, thereby reducing the hydrogen production performance.
Claims
1. A MoS2 / CdS composite photocatalyst, characterized in that: The MoS2 / CdS composite photocatalyst is a composite material that uses cadmium acetate as a cadmium source, thioacetamide as a sulfur source, and ethylenediamine as a reaction solvent to synthesize CdS nanorods through a one-step hydrothermal method, and then grows a MoS2 co-catalyst at one end of the CdS nanorods.
2. The MoS2 / CdS composite photocatalyst according to claim 1, characterized in that: The molar ratio of the cadmium acetate to thioacetamide is 1:
2.
3. The MoS2 / CdS composite photocatalyst according to claim 1, characterized in that: The loading amount of MoS2 on the CdS nanorods is 10.3wt% to 46.2wt%.
4. A method for preparing the MoS2 / CdS composite photocatalyst according to claim 1, characterized in that: The following steps are involved: Step (1), preparation of CdS nanorods: using cadmium acetate as a cadmium source, thioacetamide as a sulfur source, and ethylenediamine as a reaction solvent, dissolving cadmium acetate and thioacetamide in ethylenediamine, and performing a hydrothermal reaction. After the reaction is completed, separating the precipitate, and washing it with deionized water and anhydrous ethanol, respectively, to obtain CdS nanorods; Step (2), preparation of MoS2 / CdS composite photocatalyst: dispersing CdS nanorods in a mixed solvent of water and diethylenetriamine, adding ammonium tetrathiomolybdate as a molybdenum source and a sulfur source, reacting under high temperature conditions, separating the product after the reaction is completed, washing the product with deionized water and anhydrous ethanol, and drying; placing the product in a tubular furnace, and performing heat treatment with nitrogen as the reaction atmosphere to obtain a MoS2 / CdS composite photocatalyst.
5. The method for preparing the MoS2 / CdS composite photocatalyst according to claim 4, characterized in that: In step (1), the temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 18 hours.
6. The method for preparing the MoS2 / CdS composite photocatalyst according to claim 4, characterized in that: In step (2), the mass ratio of ammonium tetrathiomolybdate to thioacetamide is 0.15:1 to 0.70:
1.
7. The method for preparing the MoS2 / CdS composite photocatalyst according to claim 4, characterized in that: In step (2), the reaction temperature is 180° C. and the reaction time is 20 hours.
8. The method for preparing the MoS2 / CdS composite photocatalyst according to claim 4, characterized in that: In step (2), the product is placed in a tubular furnace, with nitrogen as the reaction atmosphere, and the temperature is increased to 400° C. at a heating rate of 5° C. / min, and heat treated at 400° C. for 2 hours.
9. Use of the MoS2 / CdS composite photocatalyst according to claim 1 to decompose water molecules to produce hydrogen under light conditions.
10. A method for preparing hydrogen by catalytic decomposition of water molecules, characterized in that: include: The MoS2 / CdS composite photocatalyst according to claim 1 is added to a photocatalytic reactor, and a lactic acid solution is used as a reaction substrate. Under vacuum and light conditions, the MoS2 / CdS composite photocatalyst catalyzes the decomposition of water molecules to generate hydrogen.
Citation Information
Cited By
Method for synthesizing combined cumyl chloride through photocatalysis and cumyl benzene coupling
CN120554191A
Photoanode device for realizing carrier multiplication and manufacturing method thereof
CN121451225A
A photoanode device for realizing carrier multiplication and a manufacturing method thereof
CN121451225B
